Leakage Analysis and Solution of the RFID Analog Front-END - Lin Changlong; Ma Shiliang; Lu Xin; Sun Xinzhuo; Chen Yao; Liang Ke (Institute of Advanced Engineering and Science, 2014)
The identification and modeling of different leakage components are very important for estimation and reduction of leakage power, especially low-power applications, such as RFID chip. This paper proposes a theory about leakage mechanism of RFID chip and proves the theory. The one contribution of the paper is the proposed theory about leakage mechanism of RFID chip. The other contribution is that it proves the differences between tape-out verification results and computer simulation results and that to what degree the differences occur for different circuits. And when the source potential is much lower than the substrate potential, tape-out verification results and computer simulation results have larger differences. The test results show that the actual leakage power increases 26.3 times compares with the computer simulation results’ when the source potential is -750mV.